Campus activities and events-New campus-Cultural Night 019 (1998)
Cultural Night Aug. 1998 FSU 1. Jonah 2 the whalewatchers from Monterey 2. Cambodian Traditional music Band 3. Children's Exhibit Mery Tan, 3 1/2 years old